Keterkaitan Spasial di Enam Negara Asia: Analisis Input-Output Dunia - Muchdie, M.; Imansyah, M. Handry; Prihawantoro, Socia (UI Scholars Hub, 2020)
This paper presents spatial linkages on calculations of spill-over and feed-back effects of World input-output tables, which is aggregated specifically into six-Asian countries includes China, Indonesia, India, Japan, Korea, and Taiwan, plus Australia, United States, and the Rest of the World. The results showed that, firstly output multipliers in six Asian countries tend to increase during 2000–2014, indicating a consistent economic growth. Secondly, except China, output multipliers occurred in other countries tend to increase. Thirdly, in 2000, the United States and Japan were two countries receiving highest output spill-over. However, in year 2014, most of output spill-over moved to China. India and Indonesia received only small part of spill-over from other countries. Fourthly, the highest feed-back effect occurred in China and Japan. The smallest feed-back effect occurred in India and Indonesia. China had smallest spill-over effect but received the highest feed-back effect.